2017
DOI: 10.1021/acs.jpca.7b02044
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Ionization of Argon Dimer by Intense Femtosecond Laser Pulses

Abstract: We experimentally and theoretically studied dissociative ionization of argon dimer driven by intense femtosecond laser pulses. In the experiment, we measured the ion yield and the angular distribution of fragmental ions generated from the dissociative ionization channels of (1,1) (Ar → Ar + Ar) and (2,1) (Ar → Ar + Ar) using a cold target recoil ion momentum spectroscopy. The channel ratio of (2,1)/(1,1) is 4.5-7.5 times of the yield ratio of double ionization to single ionization of argon monomer depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…To understand this experimentally observed CEP shift between the two channels, we traced the correlated electrons and the motion of the nuclei in the combined laser and Coulomb fields by performing a 3D classical ensemble model calculation [34,52], described in the Supplemental Material [48]. As the laser intensity is well above the overthe-barrier threshold [53], the two outermost electrons are rapidly stripped from each argon atom [52].…”
Section: ¼ P Nmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand this experimentally observed CEP shift between the two channels, we traced the correlated electrons and the motion of the nuclei in the combined laser and Coulomb fields by performing a 3D classical ensemble model calculation [34,52], described in the Supplemental Material [48]. As the laser intensity is well above the overthe-barrier threshold [53], the two outermost electrons are rapidly stripped from each argon atom [52].…”
Section: ¼ P Nmentioning
confidence: 99%
“…vdW dimers are used to study photoinduced biological processes [12][13][14], photocatalytic reactions [15,16], and energy or charge transfer reactions induced by soft x-ray photons [17][18][19][20] and electron impact [21]. vdW systems are also studied with strong laser fields, but in the case of dimers with a focus on the field-driven ionization and fragmentation dynamics [22][23][24][25][26][27][28][29][30][31][32][33][34][35], or electronic energy conversion processes in the case of larger clusters [36][37][38][39][40][41]. To the best of our knowledge, strong-field driven electron transfer reactions across the system boundary from one entity to another have not been investigated, thus far.…”
mentioning
confidence: 99%
“…After the strong field interaction, a fraction of the ionized electron wave packets with near-zero kinetic energies can be trapped into high-lying Rydberg states, a process also known as frustrated field ionization [3][4][5][6][7][8][9][10][11]. Frustrated double ionization (electron trapping after double ionization) has been experimentally studied for small molecules, including H 2 and argon dimers, using Coulomb explosion imaging [4][5][6][12][13][14] and theoretically using the classical trajectory Monte Carlo method [15,16]. In these experiments the trapping process is identified by the kinetic energy released (KER) during the Coulomb explosion of the molecules.…”
mentioning
confidence: 99%
“…A widely used approach to study photoinduced intermolecular processes in femtosecond pump-probe experiments is to use small molecular van der Waals clusters and dimers as model systems [1,2]. In recent years, atomic and molecular dimers have also found increasing attention in experiments that study their ionization and fragmentation dynamics when driven by strong laser fields [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. It was demonstrated that the analysis of the momenta of photoions or photoelectrons emitted during ionization fragmentation of dimers can provide detailed insight into, e.g., the ionization dynamics [30], the structural deformation induced by the strong-field interaction [26], the influence of a nearby charge on the dissociation behavior of molecules [27], or into laser-subcycle electron transfer processes [29].…”
Section: Introductionmentioning
confidence: 99%